Jini™ Specifications, The, Second Edition - Waldo, Jim (Addison-Wesley Professional, 2000)
Built on top of the Java™ software infrastructure, Jini™ technology enables all types of services and devices to work together in a community--organized without extensive planning, installation, or human intervention. Jini technology allows the lines to blur between what is hardware and what is software by representing all hardware and software as Jini technology-enabled "services," accessible either directly or through surrogates written in the Java programming language. In a distributed system of Jini technology-enabled services, these programs interact spontaneously, enabling services to join or leave the network with ease, which allows clients to view and access available services with confidence. A system of Jini technology-enabled services can link office components such as printers, faxes, and desktop computers. Beyond these traditional networks, the technology is also ideal for building the home-based networks that are now emerging: entertainment systems, cars, smart houses, and personal computers. This book contains the formal specification for the core Jini technology, as well as specifications for local helper utilities and remote helper services. It offers a review of distributed computing fundamentals, an overview of the Jini architecture, and an introduction to the key concepts that are the source of the technology's simplicity and power--remote objects, leasing, distributed events, and a two-phase commit protocol. The formal specifications provide the definitive description of every element of the Jini architecture, including detailed information on such topics as: Jini discovery and join protocols Jini entry usage Jini distributed leasing concepts Jini distributed event programming model Jini transaction model and semantics Jini lookup service and lookup attribute schema Jini discovery, event, leasing, and join utilities Jini lookup discovery, lease renewal, and event mailbox helper services Jini device architecture 0201726173B04062001.